The labour market and fiscal impact of labour tax reductions: the case of reduction of employers' social security contributions under a wage norm regime with automatic price indexing of wages. - Koen Burggraeve; Philip Du Caju (National Bank of Belgium, 2003)
This paper investigates the possible labour market and fiscal impacts of labour tax reductions in a typically Belgian setting, i.e. a wage norm regime with automatic price indexing of wages. We consider reductions in employers' social security contributions and fiscal compensation through value added or production taxes. Reductions in employers' social security contributions can only have significant employment effects if they effectively reduce labour costs. These reductions are only partly self-financing, and the cost per job created is high. The remaining negative impact on the government budget should be compensated through an alternative means of financing this expenditure, since not-compensating for the budgetary loss is not a realistic option in the long run. For this purpose, various financing schemes can be envisaged, but an increase in value added tax and the introduction of a tax on production (mimicking environmental taxes affecting firms' production costs) are the two possibilities considered in this paper. The alternative financing mechanisms destroy some of the positive employment effects of the initial reductions. However, on balance the combined measures can create some employment without worsening the government budget balance. The reaction of wages to the reduction in employers' social security contributions and to the fiscal compensation measures proves crucial. The more the initial reductions in employers' contributions are used to finance higher gross wages, and the more the inflationary effects of fiscal compensation measures are passed on in wages, the less positive the impact on employment will be. This means that little job creation is to be expected without a special co-ordination effort between all labour market players. Labour tax reductions are by no means a substitute for other labour market reforms.
Keywords: 330; Steuerpolitik; Arbeitskosten; Beschäftigungseffekt; Sozialversicherungsbeitrag; Lohnsteuer; Belgien